Automatic Fan Control Device Assembly Using Atmega8 Microcontroller - Ajeng Tiara Wulandari; Jati Sumarah; Bagoes Bambang Prayitno (Politeknik Piksi Ganesha Indonesia, 2023)
The fan is a tool that is needed to rotate air circulation. In the market, fans are usually controlled manually by turning the control switch. The research problem is how to make a fan tool that can automatically turn on when there is a change in temperature. The purpose of this research is to facilitate users in using the fan. The method used is Research and Development. The stages of Research and Development include: data collection, design, and testing. The automatic fan control circuit consists of an atmega8 microcontroller integrated with a temperature sensor, button and relay. The circuit can display the temperature and can control the fan. The automatic fan control circuit is made on a PCB whose PCB layout is made using a computer with the PCB manufacturing process still using screen printing techniques. The conclusion is that the manufacture of automatic fan control devices integrated with temperature sensors, buttons and relays can facilitate the control of fans so that users do not need to control when the temperature changes.